Conditions of Expropriation and its Implications on Property Rights: Array - Stahi , Tatiana; Robea , Mariana (Journal of Danubian Studies and Research, 2021)
Expropriation for reasons of public utility is a frequently debated topic in the literature, but it is found that contemporary doctrine has not addressed such a current and present field before the courts, but only occasionally, which motivates us. To study its problems, in a systematic way, which aims not to omit the essential issues that could lead to an overall understanding of the phenomenon of expropriation. The importance and timeliness of the expropriation investigation for reasons of public utility lies in the fact that the institution guarantees the right of property, containing regulations regarding the expropriation, that constitute real guarantees of the right of private property. According to the fundamental law, the most severe limitations that can be brought to the property right are those regarding the forced cessions of this right, which can be achieved by expropriation for a cause of public utility, established according to the law, with right and prior compensation.